PROFILE OF ORGANIC ACIDS AND BIOACTIVE COMPOUNDS IN THE SENSORY QUALITY DISCRIMINATION OF ARABICA COFFEE - Ribeiro, Diego Egídio; Borém, Flávio Meira; Nunes, Cleiton Antônio; Alves, Ana Paula de Carvalho; dos Santos, Claudia Mendes; Taveira, José Henrique da Silva; Dias, Laryanne Lopes de Carvalho (Coffee Science - ISSN 1984-3909, 2018)
This study was conducted to investigate the potential of organic acids and bioactive compounds present in rawbeans to differentiate the sensory quality of coffee from different genotypes and processing methods. During the 2010, 2011 and 2012 crop seasons, beverage quality was analyzed, as well as the profile of organic acids and bioactive compounds caffeine, trigonelline and chlorogenic acids (3,4 and 5-CQA) in raw coffee beans from genotypes Bourbon Amarelo and Acaiá. The samples were collected in commercial fields with altitudes ranging from 932 to 1391 m, in the municipality of Carmo de Minas, MG, Brazil. Two processing methods were adopted: dry process (natural) and wet process (mechanically pulped and demucilaged coffee). All harvest and post-harvest procedures were carried out according to the main technologies for the production of specialty coffees. The sensory analysis was performed using the methodology proposed by the Specialty Coffee Association of America (SCAA). Chemical analyses were performed by High performance liquid chromatography. Data were investigated using Principal Component Analysis (PCA). The variations in the contents of organic acids and bioactive compounds were due to the coffee processing method. For genotypes Bourbon Amarelo and Acaiá, the differences in the organic acid profile, associated with caffeine, trigonelline and chlorogenic acids (3,4 and 5-CQA), were essential to differentiate the quality of mechanically pulped and demucilaged coffee. No significant differences were observed in the sensory quality of natural coffee due to the analysis of organic acids and bioactive compounds.